On the Causes of Pulsing in Continuous Turbidity Currents. Issue 11 (8th November 2018) - Kostaschuk, Ray; Nasr‐Azadani, Mohamad M.; Meiburg, Eckart; Wei, Taoyuan; Chen, Zhongyuan; Negretti, Maria Eletta; Best, Jim; Peakall, Jeff; Parsons, Daniel R.
Abstract: Velocity pulsing has previously been observed in continuous turbidity currents in lakes and reservoirs, even though the input flow is steady. Several different mechanisms have been ascribed to the generation of these fluctuations, including Rayleigh‐Taylor (RT) instabilities that are related to surface lobes along the plunge line where the river enters the receiving water body and interfacial waves such as Kelvin‐Helmholtz instabilities. However, the understanding of velocity pulsing in turbidity currents remains limited. Herein we undertake a stability analysis for inclined flows and compare it against laboratory experiments, direct numerical simulations, and field data from Lillooet Lake, Canada, and Xiaolangdi Reservoir, China, thus enabling an improved understanding of the formative mechanisms for velocity pulsing. Both RT and Kelvin‐Helmholtz instabilities are shown to be prevalent in turbidity currents depending on initial conditions and topography, with plunge line lobes and higher bulk Richardson numbers favoring RT instabilities. Other interfacial wave instabilities (Holmboe and Taylor‐Caulfield) may also be present. While this is the most detailed analysis of velocity pulsing conducted to date, the differences in spatial scales between field, direct numerical simulations, and experiments and the potential complexity of multiple processes acting in field examples indicate that further work is required. In particular, there is a need for simultaneous field measurements at multiple locations within a given system to quantify the spatiotemporal evolution of such pulsing. Plain Language Summary: Turbidity currents are dense mixtures of sediment and water that flow along the bottoms of lakes, reservoirs, and oceans. Deposits of turbidity currents can provide a continuous record of climate variations, form submarine fans, and abyssal plains, two of the largest sediment features on Earth, and create economically important sources for oil and gas. Turbidity currents supply nutrients and oxygen to deep ocean and lake basins and are the primary cause of deposition and loss of storage capacity in water reservoirs. Turbidity currents that are driven by prolonged river flow and constant supplies of suspended sediment are referred to as continuous turbidity currents and can flow for weeks to months. Continuous turbidity currents are characterized by regular fluctuations in velocity or pulsing even though the river inflow does not fluctuate. This study examines the causes of pulsing and is of practical importance because pulsing increases mixing between the river and lake or ocean and produces distinct features in the rock record. Key Points: Velocity pulsing is ubiquitous in continuous turbidity currents in Lillooet Lake and Xiaolangdi Reservoir, even though the river input is steady Stability analysis of numerical, laboratory, and field data indicates that both Rayleigh‐Taylor and Kelvin‐Helmholtz instabilities can cause pulsing Rayleigh‐Taylor instabilities result from river mouth lobes and have higher bulk Richardson numbers and smaller periods than Kelvin‐Helmholtz instabilities